Novus Actus Interveniens in The Context of Criminal Law in Indonesia - Sofian, Ahmad (Bina Nusantara University, 2016)
The doctrine of novus actus interveniens used in causation to establish the liability of the principle offender for a prohibited result. The doctrine can be used in various legal fields in both civil and criminal law. The aim of this study was finding the kind of intervention that conducted by another actor, a victim or a medical worker, a non-human agent such as an animal or nature, could influenced the judge?s decisions in determining the defendant in accordance with novus actus interveniens doctrine. The method used was the normative method. The normative method in the study of jurisprudence was a method used to study secondary data sources on some legal documents. These secondary data sources were composed of some legal materials, namely primary legal materials consisting of the KUHP (the Indonesia Penal Code) and court decisions that have permanent legal force. This study finds that the doctrine of novus actus interveniens unfortunately is not commonly used by judges, prosecutors, lawyers and legal experts in Indonesia even though it can be used to solve problems in finding material truth.